Principal Management in Enhancing Teacher Professionalism in Elementary Schools - Siti Maryam Mansuryah; Helmawati Helmawati (Papanda Publisher, 2026)
Basic education plays a strategic role in improving the quality of human resources, thereby requiring professional educators. However, the reality on the ground shows challenges such as teachers not meeting the bachelor's degree qualification and a mismatch between their educational background and the subjects they teach. This study aims to describe and analyze principal management in enhancing teacher professionalism at SDN Agrabinta and SDN Jatiwangi, focusing on the functions of planning, organizing, implementation, and evaluation, as well as the constraints and solutions. The research employed a qualitative approach with a comparative case study design, collecting data through interviews, observations, and documentation. The findings reveal two distinct management models: a pragmatic-responsive model at SDN Agrabinta focused on meeting minimum standards, and a strategic-participative model at Jatiwangi focused on capacity building and innovation. Although both face similar constraints such as limited facilities, funding, and teacher motivation, the strategic-participative management model proves more effective in fostering a culture of continuous improvement. This research concludes that the principal's leadership style is a key determinant in transforming constraints into opportunities for professional growth.